PRODUCTION OF COMPLEX BASIC ALUMINIUM CASTINGS BY MEANS OF CASTING INTO CHILL MOLD WITH APPLICATION OF SAND RODS, PRODUCED UNDER COLD-BOXAMIN-PROCESS - D. A. Kudin; B. V. Kurakevich; M. A. Sadoha; G. V. Chistjakov (Литьë и металлургия)
Embedding of the technology Cold-box-amin allowed to the enterprise to solve internal problems, concerned with the bars quality, and to increase the quality of internal cavities of chill aluminium casting up to the level of modem requirements to the exported castings as well.